A new species of the catfish genus Cordylancistrus (Siluriformes, Loricariidae) from the Magdalena River, Tolima, Colombia - Provenzano, Francisco R.; Villa-Navarro, Francisco A. (Zootaxa, 2017)
A new species of catfish is described from Colombia, and provisionally assigned to the genus Cordylancistrus. The new species is most similar to C. perijae and C. nephelion from Venezuela. The description is based on ten specimens collected from tributaries of the Magdalena River which drain the eastern slope of the Cordillera Central and the western slope of Cordillera Oriental, in the Department of Tolima. The new species is the first Cordylancistrus described from the Magdalena River basin. With this discovery, the number of Cordylancistrus species in Colombia increases to three. The geographic distribution of the species suggest that Andean orogenesis played an important role in the diversification of the group.